(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates the factors influencing sustainable tourism development in Mayem Village, Goa, using Alastair M. Morrison's 10 A framework. A mixed-methods approach was employed, including surveys and statistical analyses. The research examined the relationships between various destination attributes and tourism development. Findings indicate significant correlations between awareness, appearance, assurance, attractiveness, availability, accessibility, actions, activities, appreciation, accountability, and socio-cultural aspects with sustainable tourism development. The study provides insights for policymakers and tourism stakeholders to enhance Mayem Village's tourism potential while ensuring sustainability.